(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
After the first record from Tuscany, the eulophid leaf gall-making of eucalypts Ophelimus eucalypti (Gahan) (Hymenoptera: Eulophidae) has been found in Campania region (Southem Italy). Several plants of Eucalyptus spp. resulted heavily infested in Naples and Caserta provinces. According to the preliminary observations the eulophid overwinters as larva in the galls; pupation takes place from March. Adults emerge later on from April when new young leaves are present, in which the parthenogenetic females cau oviposit. Probably O. eucalypti develops a generation per year. The introduced pest is under study.